Neuroanatomy of FTD: Whole‐brain correlations between symptoms and pathologies. (1st February 2022) - Scarioni, Marta; Gami‐Patel, Priya; Peeters, Carel F.W.; de Koning, Florianne; Seelaar, Harro; van Swieten, John C; Rozemuller, Annemieke J.M.; Hoozemans, Jeroen J.; Pijnenburg, Yolande A.L.; Dijkstra, Anke A.
Abstract: Background: Distinct pathologies accumulate in multiple brain regions (BR) and shape the heterogeneous clinical presentation of frontotemporal dementia (FTD). It is unknown how regional pathological burden links to symptoms, what the role of co‐occurring pathologies is, and whether the localization of pathology might be a bigger contributor to symptoms than the type of pathology. Our aim is to investigate how early FTD symptoms correlate to the burden of multiple pathologies throughout the brain. Method: Post‐mortem brain tissue of frontotemporal lobar degeneration (FTLD) donors from the Netherlands brain bank was dissected into twenty standard BR and stained for TAR DNA‐binding protein 43 (TDP‐43), tau, fused‐in‐sarcoma (FUS), amyloid‐beta (Aβ), and alpha‐synuclein. The burden of each pathological protein in each BR was quantified. All clinical records were reviewed to assess psychiatric, behavioral, language, and motor symptoms in the first three years from disease onset. Whole‐brain clinico‐pathological partial correlations were assessed using the heterogeneous correlation function (R 3.6.1). The local false discovery rate threshold was set at 0.01. Result: Eighty‐eight FTLD brain donors were studied, including 46 TDP‐43, 35 tau, and 7 FUS. Significant positive partial correlations (p < 0.01) were found between hippocampal TDP‐43 pathology and hallucinations (R = 0.23), perseverative‐compulsive behavior (R = 0.25), depression (R = 0.28), and mania (R = 0.32). Tau pathology in the substantia nigra and locus coeruleus was linked to depression (R = 0.25, R = 0.24). Both TDP‐43 and Aβ in the subthalamus were associated with severe disinhibition (R = 0.23, R = 0.25), while apathy correlated with both TDP‐43 and tau burden in the parietal lobe (R = 0.27, R = 0.24). Parkinsonism was linked to TDP‐43 burden in the substantia nigra (R = 0.33). Conclusion: Neuropsychiatric symptoms of FTD are linked to pathology burden in BR beyond the frontal lobes, including subcortical structures such as the hippocampus, the substantia nigra and locus coeruleus. Co‐occurring pathologies are not simple bystanders, but could play a role in configuring FTD clinical phenotype. Different pathologies in the same BR correlate with the same symptoms.